Smart nanomedicine agents for cancer, triggered by pH, glutathione, H2O2, or H2S - Li Y (Dove Medical Press, 2019)
Yaping Li,1–3 Lu An,1–3 Jiaomin Lin,1–3 Qiwei Tian,1–3 Shiping Yang1–31Key Laboratory of Resource Chemistry of the Ministry of Education; 2The Shanghai Key Laboratory of Rare Earth Functional Materials; 3The Shanghai Municipal Education Committee Key Laboratory of Molecular Imaging Probes and Sensors, Shanghai Normal University, Shanghai 200234, People’s Republic of ChinaAbstract: Effective tumor diagnosis and therapy have always been a significant but challenging issue. Although nanomedicine has shown great potential for improving the outcomes of tumor diagnosis and therapy, the nonspecial targeted distribution of nanomedicine agents in the whole body causes a low diagnosis signal-to-noise ratio and a potential risk of systemic toxicity. Recently, the development of smart nanomedicine agents with diagnosis and therapy functions that can only be activated by the tumor microenvironment (TME) is regarded as an effective strategy to improve the theranostic sensitivity and selectivity, as well as reduce the potential side effects during treatment. This article will introduce and summarize the latest achievements in the design and fabrication of TME-responsive smart nanomedicine agents, and highlight their prospects for enhancing tumor diagnosis and therapy.Keywords: tumor microenvironment, smart nanomedicine agents, theranostic agents, smart nanoprobes, smart nanocarriers